(untitled) (World Bulletin of Public Health, 2023)
Several studies stated that hospital environment is considered as a reservoir of carbapenem resistant bacteria that contaminate and spread of these bacteria to resident patients. Infection with these bacteria associated with high mortality and morbidity. Two-hundred twenty-two swab samples were taken from different sites including wards and units of four teaching hospitals in Basrah cityIraq and cultured on chromogenic medium HiCrome resist carba agar plates (Hi Media) for detection and screening of carbapenem resistant bacteria. Bacterial isolates were directly identified through colour differentiation on this medium. One-hundred and eighty-nine isolates out of two-hundred swab samples were detected as carbapenemase producers. Carbapenemase producing bacteria belonging to Klebsiella pneumoniae (61 isolates), Escherichia coli (37 isolates, Pseudomonas aeruginosa (19 isolates), Acinetobacter baumannii (4 isolates) and unidentified bacteria (68 isolates). Antibiotic susceptibility testing (Disc diffusion method) were also done for the isolates against four carbapenem antibiotics: imipenem, meropenem, ertapenem and doripenem to determine the level of susceptibility. The results were obtained as follows: Thirty isolates out of onehundred and eighty-nine carbapenem producers showed resistance to most carbapenem groups. to four carbapenem antibiotics tested. Isolate Antibiotic susceptibility testing were determined. The results showed that 100% of the isolates were resistant to the antibiotic imipenem (30 isolates), and 26 (86.66%) isolates were resistant to meropenem. 17 (56.66%) ertapenem,11(36.66%) doripenem.